汉语附着词的中介语分析 = Interlanguage Analysis of Clitics in Chinese (Sinología hispánica. China Studies Review, 2015)
本文通过中介语分析，试图发现西班牙语母语者在习得汉语附着词时容易出现的偏误类型，并提出相应的学习策略。汉语作为典型的孤立语，句法关系及语法内涵的表达大多通过附着词的使用来实现，因此附着词的学习对于汉语学习者而言至关重要。西班牙语母语者由于受其母语正迁移影响，在“体”附着词（着、了、过）使用方面偏误较少，而在结构附着词（的、地、得）以及语态附着词（啊、呢、吧等）的使用上偏误较多。研究发现，发生偏误最多的附着词是“的、了、啊、呢”。同时，通过对学习习惯的调查发现，课堂外的沉浸式学习相对于课堂内而言，更有助于汉语学习。Through the analysis of interlanguage, thisarticle tries to detect the most frequent errorsthat Spanish speakers often make when learningthe clitics of the Chinese language. The learningof the clitics is fundamental for masteringChinese, a typical example of the isolatinglanguages. The syntactic relations andgrammatical contents of the Chinese languagehighly depend on the use of the clitics. Becauseof the positive transference from their mothertongue, Spanish speakers more or less learn theaspectual clitics well. But when it comes to thestructural and modal clitics, the result is notquite satisfactory. The most problematicclitics, according to the statistics from thisarticle, are “de, le, a, ne”. An investigation ofthe study habits is also conducted. With this,we intend to emphasize the social integrationand extracurricular efforts, which sometimeseven weigh more than the class hours, are thedeterminant factors for learning a foreignlanguage well.